Naczynie funeralne - „dymokur” znad ujścia rzeki Szamanka (środkowa Angara). Interpretacja symboliki - Dmitrijew, Paweł (Folia Praehistorica Posnaniensia, 2023)
The purpose of this article is to analyze the fumigator vessel found in one of the burials on the left mouth of the Shamanka River (Central Angara) in East Siberia in 2001. By examining the ornament in the context of the symbolic and worldview system of the Siberian peoples, an attempt is made to define its cult role. Particular importance is attached to the semantic study of the ornament, as well as its interpretation using archaeological and ethnographic analogies. The result of the work is a proposal of a construct of the function of fumigator vessels in Eastern Siberia.